Fundamentos praticados por uma equipe feminina de voleibol sub 15 durante o campeonato paranaense de 2015 - Kautzner Marques Junior, Nelson (2017)
The objective of the study was of quantify the skills practiced according the position of the volleyball player and the game system of a female team under 15 during the competition. The 19 games of the Paraná championship of 2015 were filmed and were later analyzed with a scout elaborate in the Excel 2013. Kruskal Wallis Anova detected significant difference (p0,05) of the pass and of the attack of the middle player, in the set and in the defense of the setter. The Mann Whitney U test detected significant difference (p0,05) in the pass in relation to the game system in all the sets. In conclusion, the study on the number of skills practiced by a young team is relevant for the coach elaborate the load of the session